Highly compressible, binderless and ultrathick holey graphene-based electrode architectures. (January 2017) - Lacey, Steven D.; Walsh, Evan D.; Hitz, Emily; Dai, Jiaqi; Connell, John W.; Hu, Liangbing; Lin, Yi
Abstract: Graphene is a renowned material due to its unique structural characteristics and chemical properties. By heating graphene powder in an open-ended tube furnace, a highly compressible carbon material, holey graphene (hG), can be created with controlled porosity and be further decorated with nanosized catalysts using a solvent-free procedure to impart functionality and electrocatalytic activity. For the first time, we demonstrate an additive-free, dry press method to compression mold hG-based materials into ultrathick, binderless and high mass loading architectures using a hydraulic press at room temperature. The compressibility and structure of the hG allows for fabrication of unique ultrathick electrode architectures (mixed, sandwich, and double-decker) using both hG and catalyst/hG nanohybrid materials. These high mass loading, mixed and stacked hG electrode architectures are the first of their kind and are successfully demonstrated as lithium-oxygen (Li-O2 ) cathodes. The scalable, binderless, and solventless dry press method and novel additive-free electrode architectures presented here greatly advance both electrode fabrication options, and open up new electrode designs for potential energy storage advancements. Graphical abstract: Highlights: hG is a highly compressible and readily moldable porous carbon nanomaterial. A hydraulic press compresses hG materials into high mass loading electrodes. Manipulation of catalyst placement enables advanced electrode architectures. This scalable dry press method processes carbon-based materials without additives.